Hubungan antara Libatsama Pekerja dan Tingkah Laku Inovasi Pekerja di Organisasi Xyz: [Relationship between Employee Engagement and Employee Innovative Behaviour in Xyz Organization] (Sains Humanika, 2021)
This research is aimed to study the relationship between employee engagement and employee innovation behavior at XYZ Organization. A total of 62 employees at the XYZ Organization from various departments namely administration, information technology, out-reach, in-reach and exhibition were selected as respondents. The data in this research were collected through questionnaires containing information on respondent demographic, employee engagement and employee innovation behavior. After that, the data were analyzed using the Statistical Package for Social Sciences (SPSS).  The analysis of results shows that the level of employee engagement and innovation behavior is high, while the relationship between employee engagement and employee innovation behavior at XYZ Organization is positive and strong. In addition, there are several recommendations that were provided to researchers for future research.
Keywords: Engagement, Employee Engagement, Employee Innovative Behaviour, Innovation and Organization